Cross Channel currents : 100 years of the Entente Cordiale - Mayne, Richard; Johnson, Douglas, 1925-; Tombs, Robert (Routledge, 2004)
This book explores the understandings and misunderstandings that make up the Entente Cordiale - the hundred-year relationship, as well as the everyday common interests and shared pleasures that give it substance.